2007
DOI: 10.1111/j.1600-079x.2007.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances the rewarding properties of morphine: involvement of the nitric oxidergic pathway

Abstract: Melatonin has different interactions with opioids including the enhancement of the analgesic effects of morphine and also reversal of tolerance and dependence to morphine. The present study assessed the effect of melatonin on morphine reward in mice using a conditioned place preference (CPP) paradigm. Our data showed that subcutaneous administration of morphine (1-7.5 mg/kg) significantly increased the time spent in the drug-paired compartment in a dose-dependent manner. Intraperitoneal (i.p.) administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…1998; Chetsawang and Govitrapong 2005), but this increased melatonin level and disrupted circadian rhythm was not known to persist during 60 days of protracted withdrawal. Since melatonin can enhance the rewarding properties of morphine through nitric oxide pathways, its elevation may contribute to an enhanced priming effect of even a single morphine use leading to a full relapse to addiction (Yahyavi‐Firouz‐Abadi et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1998; Chetsawang and Govitrapong 2005), but this increased melatonin level and disrupted circadian rhythm was not known to persist during 60 days of protracted withdrawal. Since melatonin can enhance the rewarding properties of morphine through nitric oxide pathways, its elevation may contribute to an enhanced priming effect of even a single morphine use leading to a full relapse to addiction (Yahyavi‐Firouz‐Abadi et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In an epilepsy model induced by pentylenetetrazole (PTZ), intraperitoneal melatonin administration (40 and 80 mg/kg) was found to significantly increase the seizure threshold of the animals through the NO/ l -arginine pathway . In further support, studies have also suggested that melatonin may enhance the antiseizure effects of morphine through the NO pathway. , …”
Section: Role Of Melatonin On the Pathological Pathways Of Epilepsymentioning
confidence: 95%
“…was performed twice a day for 17 days from PND 35 to 51. The dosing regimen of melatonin was based on previous studies ( Yamamoto and Mohanan, 2003 ; Yahyavi-Firouz-Abade et al, 2007 ) and our pilot study ( Dang et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%